Financial Literacy, Creativity, Self-Efficacy and Resilience in Student Entrepreneurial Readiness - Reditayani, Ni Kadek; Suhardi (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
Entrepreneurial readiness has emerged as a crucial personal capability for university students in facing increasingly competitive labor markets and disruptive economic changes. While financial literacy, creativity, and self-efficacy have been widely identified as determinants of entrepreneurial behavior, limited studies have examined the psychological mechanism of resilience in mediating these relationships, particularly at the pre-startup stage. This study aims to analyze the influence of financial literacy, creativity, and self-efficacy on students’ entrepreneurial readiness with resilience as a mediating variable. Using a quantitative explanatory design, survey data was collected from 176 university students interested in entrepreneurship. A structured Likert-scale questionnaire was distributed using purposive sampling, and data were analyzed using Structural Equation Modeling with a Partial Least Squares approach (SEM-PLS). The results reveal that creativity and self-efficacy significantly enhance entrepreneurial readiness, while financial literacy has only a weak effect. In addition, creativity and self-efficacy significantly improve resilience; however, resilience does not influence entrepreneurial readiness and fails to mediate the relationships among the studied variables. These findings indicate that entrepreneurial readiness among students is primarily driven by cognitive creativity and internal belief systems rather than financial knowledge or resilience. The study highlights the need for entrepreneurship education that prioritizes creativity and self-efficacy development before financial or resilience training.